Climate agreements and technology policy - Rolf Golombek; Michael Hoel (University of Oslo, Department of Economics, 2004)
We study climate policy when there are technology spillovers within and across countries, and the technology externalities within each country are corrected through a domestic subsidy of R&D investments. We compare the properties of international climate agreements when the inter-country externalities from R&D are not regulated through the climate agreement. With an international agreement controlling abatements directly through emission quotas, the equilibrium R&D subsidy is lower that the socially optimal subsidy.The equilibrium subsidy is even lower if the climate agreement does not specify emission levels directly, but instead imposes a common carbon tax.Social costs are higher under a tax agreement than under a quota agreement.Moreover, for a reasonable assumption on the abatement cost function, R&D investments and abatement levels are lower under a tax agreement than under a quota agreement. Total emissions may be higher or lower in a second-best optimal quota agreement than in the first-best optimum.
Keywords: H23; O30; Q20; Q28; Q48; 330; Climate policy; international environmental agreements; R&D Policy; technology spillovers; Klimaschutz; Umweltabkommen; Forschungs- und Technologiepolitik; Spillover-Effekt